Acceptance of Kuala Lumpur Malay’s residents towards rukyah (incantation) - Mohd Tohar, Siti Nor Azhani; Deuraseh, Nurdeng @ Nurdeen; Ab. Rahman, Amaluddin; Muhammad, Zarina (Universiti Putra Malaysia Press, 2011)
The aim of this study was to describe the acceptance of Kuala Lumpur Malay residents towards: i) treatment through rukyah (incantation), ii) traditional Malay healer (bomoh), and iii) learning of rukyah (incantation). For this purpose, 343 respondents from various backgrounds were identified using a convenient sampling technique. Taman Segambut SPPK and PPR Kg. Baru, Air Panas were randomly selected as research locations. Data were collected using a questionnaire and analyzed as a descriptive statistic. Findings indicated that the level of acceptance towards the treatment through rukyah (incantation) and the Malay traditional healer (bomoh) was moderate. Meanwhile, the level of acceptance towards learning of rukyah (incantation) was low. In conclusion, the respondents were found to accept treatments done through rukyah (incantation) and the Malay traditional healer (bomoh) moderately, but they were less acceptence towards the learning of rukyah (incantation). These bring the implications that the respondents living in the city still accept treatments through rukyah (incantation) and the traditional Malay healer (bomoh) but they are not interested in the learning of rukyah (incantation). Thus, based on the findings of the study, it is recommended that efforts which give prestige to the rukyah (incantation) be supported by all parties to maintain the practice of the Islamic medicine.